2020
DOI: 10.1371/journal.pone.0231997
|View full text |Cite
|
Sign up to set email alerts
|

A computational fluid dynamics modelling of maternal-fetal heat exchange and blood flow in the umbilical cord

Abstract: Human fetal thermoregulation, maternal-fetal heat exchange, and the role of the umbilical cord in these processes are not well understood. Ethical and technical limitations have restricted current knowledge to animal studies, that do not reflect human morphology. Here, we present the first 3-dimensional computational model of the human umbilical cord with finite element analysis, aiming to compute the maternal-fetal heat exchange. By modelling both the umbilical vein and the two umbilical arteries, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
(125 reference statements)
0
9
0
1
Order By: Relevance
“…The papers in this Collection on neurophysiology (both the psychology of neurophysiological events, and oxytocin levels related to breastfeeding and birth interventions) address some of the basic science questions that still remain to be explored in the delicate neurohormonal-psycho-social dance that labour has evolved to be [39,40]. The investigation of thermal imaging as a basis for understanding how physiological labour works is an illustration of the synthesis of knowledge across clinical practice, imaging science, and service user engagement [41,42]. Understanding how midwives work to facilitate physiological birth provides a window on techniques and practices that have, heretofore, been somewhat hidden [43].…”
Section: Implications For the Cost Birth Actionmentioning
confidence: 99%
“…The papers in this Collection on neurophysiology (both the psychology of neurophysiological events, and oxytocin levels related to breastfeeding and birth interventions) address some of the basic science questions that still remain to be explored in the delicate neurohormonal-psycho-social dance that labour has evolved to be [39,40]. The investigation of thermal imaging as a basis for understanding how physiological labour works is an illustration of the synthesis of knowledge across clinical practice, imaging science, and service user engagement [41,42]. Understanding how midwives work to facilitate physiological birth provides a window on techniques and practices that have, heretofore, been somewhat hidden [43].…”
Section: Implications For the Cost Birth Actionmentioning
confidence: 99%
“…This effect can be explained by the fact that the muscle layer of umbilical cord arteries which transport oxygen-poor blood from the fetus to the placenta are stronger than that of umbilical cord veins which provide the fetus with oxygen-rich blood. They remain open longer during a compression 32 and also have a higher blood pressure 37 , even if the differences in pressure are higher on the fetal side than on the placental side 38 . Consequently, more blood flows out of the fetus than flows into the fetus 7 , 32 .…”
Section: Reviewmentioning
confidence: 99%
“…Dieser Effekt erklärt sich dadurch, dass die Nabelarterien, die sauerstoffarmes Blut vom Fetus zur Plazenta transportieren, durch ihre Muskelschicht stabiler als die Nabelvene sind, die den Fetus mit sauerstoffreichem Blut versorgt. Sie bleiben bei einer Kompression länger durchlässig 32 und verfügen zudem über einen höheren Blutdruck 37 , auch wenn die Druckunterschiede an der fetalen Seite höher sind als an der plazentaren 38 . In der Folge fließt mehr Blut aus dem Fetus heraus als hineinfließt 7 , 32 .…”
Section: Lässt Sich Die Gefahr Einer Hypovolämie Vermindern?unclassified
“…Biomechanics studies of umbilical blood vessels have suggested an interesting function for umbilical arterial helical structure. Finite Element (FE) simulation showed that helical structures of umbilical arteries aids in maintaining feto-maternal thermoregulation in the placenta circulation (Kasiteropoulou et al, 2020 ). Interestingly, experimental study showed that umbilical venous flow resistance did not increase up to 30–50% of compression of cord which could be due to the poroelastic behaviour of Wharton Jelly (Pennati et al, 2013 ).…”
Section: Umbilical Cordmentioning
confidence: 99%